Apoptosis and Cell Cycle Pathway-Focused Genes Expression Analysis in Patients with Different Forms of Thyroid Pathology - Bilous, Iryna; Pavlovych, Larysa; Krynytska, Inna; Marushchak, Mariya; Kamyshnyi, Aleksandr (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Thyroid hormones are key regulators of essential cellular processes including proliferation, differentiation, and finally apoptosis. AIM: The aim of study was to detect changes in the expression of apoptosis and cell cycle pathway-focused genes in patients with different forms of thyroid pathology. PATIENTS AND METHODS: 36 patients with thyroid pathology were enrolled in the study. We used the pathway-specific real-time PCR array (Neurotrophins and Receptors RT2 Profiler PCR Array, QIAGEN, Germany) to identify and verify apoptosis and cell cycle pathway-focused genes expression in patients with postoperative hypothyroidism, hypothyroidism as a result of autoimmune thyroiditis (AIT) and AIT with elevated serum an anti-thyroglobulin (anti-Tg) and anti-thyroid peroxidase (anti-TPO) antibodies. RESULTS: It was shown that patients with elevated serum anti-Tg and anti-TPO antibodies and with hypothyroidism resulting from AIT had a significantly lower expression of FAS, TGFB, TP53, TGFA, while the expression of CD40 was increased. The mRNA levels of BCL2 and BAX decreased in the patients with elevated serum anti-Tg and anti-TPO antibodies and increased in the patients with hypothyroidism resulting from AIT and postoperative hypothyroidism. The patients with hypothyroidism resulting from AIT and postoperative hypothyroidism had significantly lower expression of HSPB1. NF1 expression did not change in all groups of patients. CONCLUSION: The results of this study demonstrate that AIT and hypothyroidism affect the mRNA-level expression of apoptosis and cell cycle pathway-focused genes in gene specific manner and that these changes to gene expression can be responsible for the apoptosis signs and symptoms associated with thyroid pathology.